المدونة المسرحية بين صناعة النص وسلطة التأويل: دراسة تاريخية - الخميس، علي عبد الأمير عباس فهد (جامعة عمار ثليجي بالأغواط - كلية العلوم الإنسانية والعلوم الإسلامية والحضارة - قسم العلوم الإسلامية, 2022)
باتت سلطة التأويل الإخراجية في متابعة حركة المعنى لدى النص المسرحي (المرجع)، وإظهار التوسطات الجديدة التي يقيمها الخطاب بين الإنسان والعالم، ما هو إلا رؤية ممهدة لرؤيا سابقة يستدل بها من خلال (العلامة، والمدلول، والاستعارة، والرمز، والنظام) عن معنى جديد لمعنى قديم، فلا يمكن التوقف عند المعنى الأول والثاني، وهكذا تباعا، فالتأويل متمثلا بسلطته هو فن امتلاك الشروط الضرورية للفهم. The power of directional interpretation follows the movement of meaning in the theatrical text (reference) and shows the new mediations which are established by the discourse between man and the world. It is only a vision paving the way to a previous one that is inferred through (sign, meaning, metaphor, symbol and system). It is a new meaning for an old meaning on the basic ground that it is not possible to stop at the first and second meanings, and thus, respectively, the interpretation represented by its authority is the art of possessing the necessary conditions of understanding.
Keywords: النصوص المسرحية -- الفنون الثقافية -- الأدب المسرحي